Pengembangan Keterampilan Multimedia Mahasiswa PGMI Melalui Pembelajaran Berbasis Proyek Komik Video Digital - Irma Indriani (Fusshilat : Jurnal Studi Pendidikan dan Keislaman, 2026)
This study aims to analyze the development of multimedia skills among PGMI students through project-based learning using Digital Video Comics (KOVID) in the Elementary School Instructional Media course. This study employed a qualitative descriptive method, involving 15 seventh-semester students and 10 students selected through purposive sampling as informants. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. The results indicate that project-based learning through KOVID is effective in enhancing students’ multimedia skills, particularly in scriptwriting, visual design, audio recording, and video editing. A total of 12 out of 15 students showed significant improvement in producing integrated multimedia products. Additionally, there was an increase in students’ creativity, critical thinking, and self-confidence. This study contributes to the development of an innovative learning model that integrates project-based learning with digital media in madrasah teacher education.